Pengaruh Kepemimpinan Birokrasi, Pelatihan, Kemampuan Kerja Dan Kualitas Kehidupan Kerja (Qwl) Terhadap Kinerja Pegawai Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Labuhanbatu - Novio Helda; Umarnuddin; Irwan; Muhammad Rasyid Harahap; Yanis Zawawi; Supar Wasesa (Journal of Trends Economics and Accounting Research, 2022)
This study aims to determine the effect of bureaucratic leadership, training, work ability and quality of work life (QWL) on employee performance at the Investment and One-Stop Integrated Service Office of Labuhanbatu Regency. This type of research is Associative Research. Data collection in this study was carried out through a survey approach with quantitative descriptive research type by distributing questionnaires to 46 respondents, while the population used in this study were employees of the Investment and One Stop Service Office of Labuhanbatu Regency. Data collection techniques were carried out by interviews, questionnaires and documentation studies. The data analysis tool used in this study uses SPSS (Statistical Product Software Solution). Data analysis in this study is descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significant test (t test), simultaneous significant testing (F test), and testing the coefficient of determination (R2). The results of this study indicate that partially (t test) it is known that bureaucratic leadership has a positive and significant effect on employee performance. The training variable has a positive and significant effect on employee performance. Workability variable has a negative and significant effect on employee performance. Then the Variable Quality of Work Life has a positive and significant impact on employee performance at the Office of Investment and One-Stop Integrated Services, Labuhanbatu Regency. In simultaneous testing (F test) it is known that Bureaucratic Leadership, Training, Work Ability and Quality of Work Life have a positive and significant effect on Employee Performance at the Investment and One Stop Service Office of Labuhanbatu Regency.